SAR Measurement from Mobile Phone and Its Effect to Human Body - Ahmad, Noor Azlinda; Shaharun, Putri Fhazleen (ELEKTRIKA- Journal of Electrical Engineering, 2023)
Electromagnetic fields are created by radiofrequency waves. However, the RF emitted by a mobile phone's antenna is insufficient to cause significant heating of tissues in the ear or head. The focus of this research is to look further into SAR measurement of how much RF radiation is absorbed by tissues in the human body. A CST Microwave studio, a high-performance 3D EM analysis software, is used for this project to design, analyse, and measure electromagnetic (EM) components and systems, and perform SAR calculation as a post-processing step after the simulation. It is shown in the result that the human body does absorb energy from radiofrequency radiation emitting devices. Heating to the area of the body where a cell phone is held is the only consistently recognized biological effect of radiofrequency radiation absorption in humans, but heating is insufficient to measurably increase the body temperature.